PENAMBAHAN SELULOSA KULIT PINANG PADA PEMBUATAN PLASTIK BIODEGRADABLE PATI BIJI ALPUKAT - Luqmanul Hakim; Yelmira Zalfiatri; Yossie Kharisma Dewi (Fakultas Pertanian Universitas Riau, 2025)
Biodegradable plastic is a type of plastic made from renewable materials and can be produced using materials containing starch, such as in avocado seeds. However, starch-based biodegradable plastic has the disadvantage of low mechanical properties, such as tensile strength and elongation; therefore, it is necessary to add reinforcement, such as cellulose. One potential source of cellulose with a relatively high content is areca nut skin. This study aims to obtain the appropriate concentration of areca nut skin cellulose for the characteristics of biodegradable avocado seed starch plastic. A completely randomized design (CRD) with five treatments and three replications was used in the experimental procedure of the investigation. The treatments in this study were the addition of cellulose S1 (3 g), S2 (4 g), S3 (5 g), S4 (6 g), and S5 (7 g), and the measured characteristics were water absorption, water vapor transfer rate, tensile strength, elongation, and biodegradability. The data obtained were analyzed statistically using analysis of variance (ANOVA). The results showed that the addition of areca nut cellulose significantly affected the water absorption capacity, water vapor transfer rate, tensile strength, elongation, and biodegradability of biodegradable plastics. The selected biodegradable plastic was treatment S1 (3 g), which showed a water absorption capacity of 58.80%, a water vapor transfer rate of 17.03 g/m²/hour, a tensile strength of 30.73 MPa, an elongation of 9.31%, and biodegradability of 44.24%.